Gambaran sefalometri pasien usia 8-11 tahun menggunakan analisis jarabak - Hobibah Muqodariah, Ratu; Piona Sahelangi, Olivia (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Cephalometry used to determine growth patterns and study craniofacial structures. Jarabak analysis, interprets the morphological characteristics of the mandible with other craniofacial structures. Objective: Obtain the mean value of cephalometric measurements based on Jarabak analysis in orthodontic patients aged 8-11 years at RSGM-P FKG Usakti. Methods: Descriptive observational research by tracing 104 cephalograms each consisting of 52 female and male. Results: The mean values of female angle measurements are, saddle angle 126˚ articulare angle 143˚ gonial angle 131˚ Jarabak sum 399˚ upper gonial angle 53˚ lower gonial angle 78˚. Linear measurements obtained the value of S N 58mm Go Me 57mm S Ar 28mm Ar Go 34mm S Go 59mm N Me 99mm, Jarabak ratio 59%. The mean values in male angle measurements are, saddle angle 124˚ articulare angle 143˚ gonial angle 130˚ Jarabak sum 399˚ upper gonial angle 53˚ lower gonial angle 77˚. Linear measurements obtained the value of S N 59mm Go Me 58mm S Ar 29mm Ar Go 35mm S Go 61mm N Me 99mm, Jarabak ratio 61%. Conclusion: Three female and male angular measurements, and one male linear measurement were equal to the Jarabak analysis norms. One female and one male linear measurement was greater than the Jarabak analysis norm.